Early Warning System Of Water Quality Changes In Fishponds - Muhammad Asep Subandri; Danuri Danuri (Universitas Islam Kuantan Singingi, 2023)
This study aims to develop an early warning system for changes in water quality in fish ponds using the MQTT and Telegram Bot protocols. Poor water quality can cause significant economic losses in fish farming. Therefore, a system is needed that can accurately and quickly detect changes in water quality and provide warnings to fish farmers. The method used in this study involves the installation of sensors that are connected to a microcontroller and a communication system using the MQTT protocol. The sensors used include temperature sensors, pH sensors, turbidity sensors, water level sensors, and salinity sensors. The data obtained from these sensors will be sent via the MQTT protocol to the server connected to Telegram Bot. Telegram Bot is used as an interface for users. This bot will receive data from the server and perform processing to evaluate the water quality in fish ponds. If a significant change in water quality parameters is detected, the bot will send an early warning to fish farmers via Telegram messages. Fish farmers can receive these alerts on their mobile devices, so they can quickly take the necessary action to improve water conditions. The results of this study indicate that the developed early warning system can provide fast and accurate warnings of changes in water quality in fish ponds. With this system, fish farmers can take the necessary actions to prevent losses caused by changes in water quality before more serious damage occurs. In addition, the use of Telegram as a communication platform allows fish farmers to receive alerts on their mobile devices, which increases the responsiveness and convenience of water quality monitoring.